2007
DOI: 10.1111/j.1365-2133.2007.07827.x
|View full text |Cite
|
Sign up to set email alerts
|

Sclerodermatous graft-versus-host disease: clinical spectrum and therapeutic challenges

Abstract: Sclerodermatous graft-versus-host disease (GVHD) is a rare complication of bone marrow transplantation. While GVHD is often associated with the beneficial graft vs. tumour effect, it also contributes towards significant morbidity and mortality. No reliably effective treatment has yet been established. We present 10 patients with haematological malignancies who underwent an allogeneic stem cell transplant and developed sclerodermatous GVHD. Donor lymphocyte infusion administered for relapse or reducing donor T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…For chronic GvHD, PUVA treatment was reported to be more effective with the lichenoid form of the disease; with improvement in sclerotic GvHD reported in some instances. 5,46 However it was also reported that after the PUVA treatment was ceased the lesions returned. 40 UVA1 Three studies were identified that utilised UVA1 in the treatment of chronic cutaneous GvHD.…”
Section: Chronic Gvhdmentioning
confidence: 93%
“…For chronic GvHD, PUVA treatment was reported to be more effective with the lichenoid form of the disease; with improvement in sclerotic GvHD reported in some instances. 5,46 However it was also reported that after the PUVA treatment was ceased the lesions returned. 40 UVA1 Three studies were identified that utilised UVA1 in the treatment of chronic cutaneous GvHD.…”
Section: Chronic Gvhdmentioning
confidence: 93%
“…However, the clinical spectrum of cGVHD is broad [25,26] and it can include poikiloderma, xerosis, annular scleroderma-like lesions, keratosis pilaris-like lesions, psoriasiform lesiones, deep sclerotic features, eccema-like lesions, acral erythema, fasciitis, morphea-like superficial sclerotic features, and/or lichen sclerosus-like [1,7,10,24,27].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Sclerodermatous GVHD is characterized by hypo or hyperpigmented thickened, tight, indurated and fragile skin which is often associated with poor wound-healing, inadequate lymphatic drainage, skin ulcers from minor trauma, contractures and limited joint mobility [10,24,25]. Characteristically, these lesions tend to appear on sites of minor skin trauma or pressure (waistband line, brassiere line) or on sites of previous skin damage (such as old scars or site of a previous herpes zoster infection) [10].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Due to the paucity of microarray data for standalone meta-analysis of cGVHD, we used similarities in systemic responses between cGVHD and systemic sclerosis (SSc) to link their microarray datasets [5,6]. The similarity in systemic responses between cGVHD and SSc was demonstrated in the experimental settings and was attributed to the excessive activation of T and B cells in both conditions [7].…”
Section: Introductionmentioning
confidence: 99%